PROLAKTİNOMALI HASTALARDA FİBROBLAST BÜYÜME FAKTÖRÜ-23 VE ALFA KLOTHO DÜZEYLERİNİN ARAŞTIRILMASI - ARI, FATMA ZEHRA YILDIRIM (Fırat Üniveristesi, 2025)
Prolaktinoma, hipofiz bezinin en sık görülen hormon aktif tümörlerinden biridir ve genellikle hiperprolaktinemi ile seyretmektedir. Prolaktin fazlalığı, metabolik süreçler üzerinde de etkili olmaktadır. Bu çalışmada prolaktinoma ve hiperprolaktinemi tanılı bireylerde Alfa-Klotho (?-Klotho) ve Fibroblast Büyüme Faktörü-23 (FGF-23) düzeyleri arasındaki ilişkinin araştırılması amaçlanmıştır. Literatür taranmasında prolaktinomalı hastalarda FGF-23 ve ?-Klotho düzeylerini araştıran bir çalışmanın yapılmadığı görülmüştür. Bu amaç doğrultusunda 30 sağlıklı birey, 29 prolaktinomalı hasta ve 14 hiperprolaktinemili hasta olmak üzere toplam 73 kişinin kan örneklerinde çalışma yapılmıştır. FGF-23 ve ?-Klotho protein düzeyleri Enzim Bağlantılı İmmünosorbent Testi (ELISA) yöntemi ile ölçülmüştür. Serum FGF-23 ve ?-Klotho düzeylerinin prolaktinomalı ve hiperprolaktinemili hastalarda sağlıklı kontrol grubuna göre anlamlı düzeyde arttığı görülmüştür (p<0.05). Proaktinomanın tanı ve takibinde genellikle MR çekimi ile yapılmaktadır. FGF-23 ve ?-Klotho düzeylerinin proaktinomalı hastaların tanı ve takibinde kullanılmasının spesifikliği ve duyarlılığı ROC ile bakılmış ve yüksek olduğu tespit edilmiştir. Prolaktinomalı daha fazla hasta ile yapılacak çalışmalar ile FGF-23 ve ?-Klotho düzeyleri ölçülerek hem tanı hem de tedavi takibi yapılabilir. Prolaktinoma tanılı hastalarda FGF-23 ve ?-Klotho ölçülmesi ile ilgili daha çok hastanın yer aldığı çalışmalar yapılamalıdır.

Prolactinoma is one of the most common hormone-active tumors of the pituitary gland and generally presents with hyperprolactinemia. Prolactin excess also impacts metabolic processes. This study aimed to investigate the relationship between Alpha-Klotho (?-Klotho) and Fibroblast Growth Factor-23 (FGF-23) levels in individuals diagnosed with prolactinoma and hyperprolactinemia. A literature review revealed no studies investigating FGF-23 and ?-Klotho levels in patients with prolactinoma. For this purpose, blood samples from a total of 73 individuals were studied: 30 healthy individuals, 29 patients with prolactinoma, and 14 patients with hyperprolactinemia. FGF-23 and ?-Klotho protein levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA). It was observed that serum FGF-23 and ?-Klotho levels were significantly increased in patients with prolactinoma and hyperprolactinemia compared to the healthy control group (p<0.05). The diagnosis and follow-up of prolactinoma are generally carried out by MRI. The specificity and sensitivity of using FGF-23 and ?-Klotho levels in the diagnosis and follow-up of patients with prolactinoma were evaluated with ROC analysis and found to be high. By conducting studies with a larger number of prolactinoma patients, the measurement of FGF-23 and ?-Klotho levels could be used for both diagnosis and treatment monitoring. Further studies involving a greater number of patients are needed to evaluate the role of FGF-23 and ?-Klotho measurements in prolactinoma.
The investigation of alpha klotho and FGF-23 levels in prolactinoma's disease
Keywords: Biyokimya